2014
DOI: 10.1109/tla.2014.6893996
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of the Electric Energy Distribution using Data Envelopment Analysis with undesirable outputs

Abstract: In this paper we propose to use Data Envelopment Analysis (DEA) to assess the efficiency of twenty electricity distributors in Brazil. Among the variables chosen to perform this study, we have chosen some distributors' undesirable results, which in DEA are called undesirable outputs that need to be included. We use and discuss some approaches to deal with these types of variables. To determine a ranking for the electricity distributors we also use Inverted Frontier and the composed efficiency index, which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
0
7
0
1
Order By: Relevance
“…3), as well as DMUs that presented inefficiency in the input-oriented CRS model. In this model the proportionality principle is applied and any variation in inputs implies the proportional variation of outputs (Tschaffon and Meza, 2014). In assessing the input-oriented CRS model standard efficiency in 2014 (Fig.…”
Section: Crs (Constant Returns To Scale) Results Of 2014 and 2016mentioning
confidence: 99%
“…3), as well as DMUs that presented inefficiency in the input-oriented CRS model. In this model the proportionality principle is applied and any variation in inputs implies the proportional variation of outputs (Tschaffon and Meza, 2014). In assessing the input-oriented CRS model standard efficiency in 2014 (Fig.…”
Section: Crs (Constant Returns To Scale) Results Of 2014 and 2016mentioning
confidence: 99%
“…This can be very useful when we have few DMUs to analyze that almost all efficient and we need to have a benchmark, for instance, for regulation of public fares. Regulation of public fares using DEA was done in Thanassoulis et (2000), Tschaffon and Angulo-Meza (2014) and Andrade et al (2014), for instance.…”
Section: Discussionmentioning
confidence: 99%
“…This can be very useful when we have few DMUs to analyze that almost all efficient and we need to have a benchmark, for instance, for regulation of public fares. Regulation of public fares using DEA was done in Thanassoulis et (2000), Tschaffon and Angulo-Meza (2014) and Andrade et al (2014), for instance.Therefore, the aim of this work was to determine the dual formulation for the MCDEA model, to study their properties and suggest benchmarks for the inefficient DMUs. To do so, we restrain ourselves to study the partial MCDEA model, i.e., models with only two objective functions.…”
mentioning
confidence: 99%
“…In Tschaffon and Meza (2014) study, in which 20 Brazilian electricity distributors were analyzed in 2008, COELBA was the only company considered efficient and we identified COELBA as the company with the lowest efficiency score. Pinheiro (2012), when conducting an evaluation of Aneel's ranking (DGC-based ranking) for electricity distributors, found that efficient distributors generally present better performance in cost or quality.…”
Section: Graph 1 -Total Potential Improvements (%)mentioning
confidence: 99%